Quantum transport in one-dimensional GaAs hole systems. (31st January 2008) - Hamilton, A.R.; Klochan, O.; Danneau, R.; Clarke, W.R.; Ho, L.H.; Micolich, A.P.; Simmons, M.Y.; Pepper, M.; Ritchie, D.A.; Muraki, K.; Hirayama, Y.
In many advanced semiconductor devices, the physical dimensions are sufficiently small that quantum physics becomes important in determining the device behaviour. A celebrated example is the quantum wire, where in the absence of scattering the conductance is quantised in units of 2e²/h. Although electron quantum wires have been studied extensively for almost two decades, the development of hole quantum wires has been a significant challenge, limiting studies of hole-based devices. Here we review our recent work on hole quantum wires, and show how they can be used to probe the spin properties of hole systems. The ability to fabricate ballistic quantum wires, and control their spin properties using electrical gate biases, may have implications for future spintronic devices.